NiFe2O4 / rGO nanocomposites produced by soft bubble assembly for energy storage and environmental remediation. (January 2022) - Tamilselvi, R.; Lekshmi, G.S.; Padmanathan, N.; Selvaraj, V.; Bazaka, O.; Levchenko, I.; Bazaka, K.; Mandhakini, M.
Abstract: Environmental concerns regarding the use of potentially harmful chemicals and fossil fuels stimulate research efforts on the multifunctional hybrid nanocomposites produced from biowastes via simple environmentally friendly processes. Such nanomaterials could help to combat the escalating environmental issues related to environmental remediation and energy storage, as a step to the renewable energy technology of the future. This work discusses the synthesis of novel nickel-based reduced graphene oxide (rGO) nanostructured composites with superior energy storage and photocatalytic properties. Using a facile hydrothermal method, rGO nanoflakes were synthesized from the negative value coconut coir biowaste and then decorated with functional NiO and NiFe2 O4 nanoparticles to produce hierarchical functional nanocomposites. Benefiting from the synergies arising from the concomitant use of NiFe2 O4 nanoparticles and rGO nanoflakes, the resultant nanocomposites yielded excellent specific capacitance of 599.9 F/g at current density of 1 Ag -1 and retention rate of 86.5% even after 2000 cycles. Moreover, the composite exhibited excellent efficiency of visible light driven photocatalytic degradation of 96.5%. Thus, our material is essentially multifunctional and importantly, it demonstrates quite pronounced electrochemical and photocatalytic activities when produced in a simple, single technological route. These findings confirm that the developed multifunctional nanostructured composite is a strong candidate material for energy and environmental remediation applications. Highlights: Reduced graphene oxide nanocomposite was synthesized via facile hydrothermal route. Negative value coconut coir biowaste was used as a precursor. Nanocomposites were decorated with functional NiO and NiFe2O4 nanoparticles. Nanocomposites feature superior energy storage and photocatalytic properties. This material is multifunctional, produced in a single technological route.